Trajectory of a ball on an inclined plane. (1st September 2022) - Cross, Rod
Abstract: The trajectory of a ball rolling across an inclined plane was recorded on video film to determine if it followed a parabolic path as others have suggested. The challenges in this case were (a) to determine the magnitude and direction of the friction force on the ball, (b) to determine the effect of the friction force on the trajectory and (c) to explain why the rotation axis of the ball rotates as it rolls up and down the incline. The experiment is a simple extension of standard inclined plane experiments but with the extra pedagogical feature that angular velocity sometimes needs to be treated as a vector quantity.